2015
DOI: 10.5395/rde.2015.40.4.306
|View full text |Cite
|
Sign up to set email alerts
|

Identification ofEnterococcus faecalisantigens specifically expressedin vivo

Abstract: ObjectivesMolecular mechanism of the pathogenicity of Enterococcus faecalis (E. faecalis), a suspected endodontic pathogen, has not yet been adequately elucidated due to limited information on its virulence factors. Here we report the identification of in vivo expressed antigens of E. faecalis by using a novel immunoscreening technique called change-mediated antigen technology (CMAT) and an experimental animal model of endodontic infection.Materials and MethodsAmong 4,500 E. coli recombinant clones screened, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…70 This Gram-positive commensal bacterium belongs to the lactic acid bacteria (LAB), it is a facultative anaerobic, resistant to extreme environmental challenges and is usually found in the human oral cavity, GI and vagina mucosa. 71 However, it can emerge as a human pathogen of significant concern 72 and so can be associated with various pathologies including urinary tract infections, 73 endocarditis, 74 persistent endodontic diseases, 75 blood stream infections 76 and chronic periodontitis. 77 E. faecalis is the first colonizer of the human GI tract and has a major impact on intestinal immune development in the very early stages of life.…”
Section: General Aspects Of Gut Microbiotamentioning
confidence: 99%
“…70 This Gram-positive commensal bacterium belongs to the lactic acid bacteria (LAB), it is a facultative anaerobic, resistant to extreme environmental challenges and is usually found in the human oral cavity, GI and vagina mucosa. 71 However, it can emerge as a human pathogen of significant concern 72 and so can be associated with various pathologies including urinary tract infections, 73 endocarditis, 74 persistent endodontic diseases, 75 blood stream infections 76 and chronic periodontitis. 77 E. faecalis is the first colonizer of the human GI tract and has a major impact on intestinal immune development in the very early stages of life.…”
Section: General Aspects Of Gut Microbiotamentioning
confidence: 99%
“… 258 • Requires significant surgical intervention • Blood can be sampled over a time course without sacrificing animal • Ethical concerns about using companion animal species for research • Genetically modified animals are less common compared with mice • Higher costs are associated with housing larger animals Endodontic infection : Endodontic infection : • Acquisition of larger samples for analysis compared with smaller animals. 184 • Surgical procedures requires technical expertise Zebrafish General advantages : General disadvantages • Cheapest vertebrate organism • Difficulties in translating host response to mammalian infections due to high degree of evolutionary divergence. • Amenability to scaling up • Difficult to create truly inbred zebrafish lines • Transparent body allows in vivo imaging of host-pathogen interactions Invertebrates C. elegans General advantages : General disadvantages : • Smallest in size (adults are ∼1mm) among the 3 invertebrates • Lack cellular and humoral system • Low cost • Lack of a fully sequenced genome • Rapid life cycle (∼3.5 days at 20°C) • Infection cannot be performed at 37°C • Transparent body and genetic tractability • Not as readily available as compared with G. mellonella • Easiest to maintain in large-scale quantity • Excellent choice to investigate gut microbial-host infection G. mellonella General advantages : General disadvantages : • Have cellular and humoral immune system • Lack of a fully sequenced genome ...…”
Section: Enterococcal-associated Polymicrobial Infectionsmentioning
confidence: 99%
“…Infected premolars are extracted and hemisectioned, infected pulp and periapical tissues removed, and bacterial cell pellets are saved for hyperimmune antisera production in rabbits. 184 This study identified 16 in vivo -induced protein antigens involved in housekeeping functions, metabolism, and cellular processes. Potential virulence factors include a copper resistance protein that could confer resistance to metallic copper-coated antimicrobial surfaces and several putative membrane proteins of unknown function.…”
Section: Vertebratesmentioning
confidence: 99%
See 1 more Smart Citation